EKSPLORASI DATA ARKEOLOGI DI KAWASAN LERENG TIMUR GUNUNG MERAPI KABUPATEN BOYOLALI, JAWA TENGAH - Sugeng Riyanto (Berkala Arkeologi, 2011)
Boyolali District geographic area covers the eastern slopes of Mount Merapi (and Merbabu). In the archaeological area is very important as an area that holds relics of archaeological data with a fairly long time span. On the other hand, concern over this region has not been for the region south and west slopes are academically have contributed information and past knowledge of the Indonesian people, especially from the classical period (eighth century - XM), Islamic period (beginning of the sixteenth century AD), until colonial period (about XVII century - beginning of XX century AD). Therefore it was not excessive if the research activities through archaeological exploration in the eastern slopes of Mount Merapai is a momentum to the rise of attention to archaeological data in the region, to contribute information and knowledge within the framework of ideological development, the development of scientific value, as well as the approaches to extracting value -economic values